A Cross-Sectional Study to Understand Socio Demographic Profile of Couples Who Adopted Permanent Sterilization in Urban Slums of Surat City - Parmar, Ketan B; Kantharia, S L; Godara, Naresh R; Shah, Hitesh M; Patni, MohamedAnas M (National Journal of Community Medicine, 2013)
Introduction: There is big gap in the adoption of male and female sterilization. It is necessary to understand socio demographic factors of couples who adopted permanent sterilization. Aims & Objectives: The study was done with the aim to document the socio demographic profile of couples who adopted permanent sterilization in urban slums of Surat city. Material and Methods: It was a cross sectional study conducted during March-April 2011 in urban slums of Surat City. 532 couples who adopted permanent sterilization were interviewed for their socio demographic profile. Results: Maximum males and females in our study who had adopted permanent sterilization operation were in age group of 30-34 yrs and 25-29 yrs respectively. 40.6% of couples were from joint family and 59.4% were from nuclear family. 58.83% of the families of study couples had family members of 4-6 persons. Literacy rate in studied population was 68.43% among males and 58.64% among females, with maximum no. of respondents had studied up to primary level education in both male and female. male sterilization is more common in Hindus as compared to Muslims. Males were more dominant than female regarding decision making for contraceptive use. Conclusion: Female sterilization was more common in families with low socio economic status, low literacy and Muslim families. While male sterilization was more common in Hindu families and where husbands have high literacy levels.